Ecofeminist Tendencies in Virginia Woolf, Doris Lessing and Arundhati Roy - Kaosar Ahmed, Mohammad (International Journal of English Literature and Social Sciences (IJELS), 2019)
Ecofeminists investigate the joint abuse of women and nature, and urge people to give more consideration to the inexorably pulverized condition of women and nature. In the perspective of ecofeminists, patriarchy is the main driver of women persecution just as the nature abuse. Woolf, Lessing and Roy have an identical pursuit with that of ecofeminism. With themes consistent with those of ecofeminists, they attempt to explore the universal relationship between degrading female and nature, and advocate building a brand-new relationship between mankind and nature.